Relationship between polimorphisms of PLIN and MC4R genes with fattening qualities of pigs - Гиря, В. М.; Метлицька, О. І.; Усачова, В. Є.; Бондаренко, О. М. (Scientific Progress & Innovations, 2018)
The analysis of distribution of allelic variants of RLIN and MC4R genes in pigs of different breeds is presented. The influence of gene polymorphism on animal fattening qualities was established. The obtained research results substantially complement the scientific and cognitive basis of genetic factors that determine the level of productivity of fattening young animals and confirm the effective use of their polymorphism as DNA markers in the periodic breeding programs.